Synthesis method of surface octahedral oxygen vacancy double-shell Co3O4 catalyst with high electro-catalytic chlorine evolution selectivity

The preparation of surface octahedral oxygen vacant double-shell Co3O4 catalyst for the precursor through Co-BTC MOF, which solves the problems of high cost and side reaction of precious metal catalysts in the chlor-alkali industry, and achieves high-efficiency electrocatalytic chlorine evolution and stability, significantly improves chlorine evolution Selectivity and stability.

CN119287415APending Publication Date: 2025-01-10SHANDONG LONGANTAI ENVIRONMENTAL PROTECTION SCI TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411654316.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The precious metal catalysts used in the existing chlor-alkali industry are costly and have side reactions, resulting in low energy utilization efficiency and lack of effective non-precious metal-based high-performance chlorine-excited catalysts.

Method used

Binocarpal hollow Co3O4 nanospheres were prepared by oxidative annealing by Co-BTC MOF as the precursor, and treated in NaBH4 solution to construct a bicapillary Co3O4 catalyst with octahedral oxygen vacancy and multi-stage structure to inhibit OER reaction and improve electrocatalysis Chlorine-elimination selectivity.

Benefits of technology

High-efficiency electrocatalytic chlorine elution was achieved, with the overpotential reduced to 52 mV, and the selectivity of chlorine elution reached 98.9~99.9%, and the stability remained above 95.3%, which was better than commercial RuO2/IrO2 catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287415A_ABST
    Figure CN119287415A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional nano composite materials, and particularly relates to a synthetic method of a surface octahedral oxygen vacancy double-shell Co3O4 catalyst with high electro-catalysis chlorine evolution selectivity. Comprising the following steps: firstly, mixing cobalt nitrate hexahydrate, trimesic acid, ethanol and an ethylene glycol solvent according to a certain proportion, and carrying out solvothermal reaction to obtain a spherical Co-BTC precursor; and then the prepared Co-BTC precursor is annealed and oxidized for 1-3 h in air at a certain annealing rate of 1-5 DEG C / min in an environment of 300-500 DEG C, and the hollow double-shell structure material DS-Co3O4 is obtained. Finally, DS-Co3O4 and a sodium borohydride solution are mixed, soaked and stirred for 1-3 h, the double-shell Co3O4 nanospheres with octahedral oxygen vacancies and a multilevel structure are obtained, and high-selectivity electro-catalysis chlorine evolution reaction can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional nanocomposite materials, and specifically, discloses a method for synthesizing a surface octahedral oxygen vacancy double-shell Co3O4 catalyst with high electrocatalytic chlorine evolution selectivity. Background Art

[0002] Chlorine is one of the most important consumer chemicals, with an annual demand of about 88 million tons. It has been widely used in pharmaceutical engineering, polymer functions, wood bleaching and wastewater treatment. To meet the market demand for Cl2, the chlor-alkali industry consumes more than 20 billion kWh of electricity each year. From the perspective of energy storage mechanism, the main strategies to reduce energy consumption include reducing the cell pressure of the electrolyzer and improving the Coulombic efficiency. For example, the use of commercial catalysts based on ruthenium dioxide / iridium dioxide (DSA) instead of traditional graphite rod electrodes as anodes can reduce the overpotential of the CER process and achieve a significant reduction in the cell pressure. However, Ru and Ir are low in content in the earth's crust and are expensive, resulting in higher production costs. In addition, a side reaction, oxygen evolution reaction (OER), will occur during the chlorine evolution reaction, and the OER potential is 1.23 V, which is lower than the CER potential of 1.36 V. The OER reaction is more likely to occur, resulting in reduced energy utilization efficiency. Therefore, the development of non-precious metal-based CER catalysts with excellent activity, kinetics and excellent selectivity is an important measure to reduce production costs, accelerate the chlorine evolution reaction, and help the chlor-alkali industry.

[0003] Cobalt tetroxide has a spinel structure, which consists of two tetrahedral coordinated Co 2+ and octahedral coordinated Co 3+ and tetrahedrally coordinated O 2- The two structures are composed of Co3O4 and Co2O4, and they have excellent catalytic performance in many catalytic reactions. Therefore, they are widely used to replace precious metal catalysts in the fields of electrocatalysis, photocatalysis and thermal catalysis. Studies have shown that Co3O4 nanostructures with different growth orientations exhibit different catalytic activities. This is mainly because the catalytic active sites of Co3O4 are octahedral sites of Co 3+ , the octahedral sites exposed in different growth orientations are different, and therefore exhibit different catalytic properties. Especially in the OER process, the octahedral catalytic sites can provide coordinated oxygen, activate the lattice oxygen reaction mechanism (LOM), significantly catalyze the reaction kinetics, and achieve a significant improvement in performance. To design a high-performance Co3O4 chlorine evolution catalyst, it is necessary to suppress its LOM mechanism and enhance the binding capacity of the octahedral central oxygen. However, to date, there is no effective strategy to improve the chlorine evolution selectivity of Co3O4. The research and development of related catalysts and mechanism exploration are of great significance for the development of a new generation of high-efficiency non-precious metal chlorine evolution catalysts. Summary of the invention

[0004] The present invention provides a method for synthesizing a double-shell Co3O4 catalyst with surface octahedral oxygen vacancies and high electrocatalytic chlorine evolution selectivity. This method uses Co-BTC MOF as a precursor, first prepares double-shell hollow Co3O4 nanospheres (DS-Co3O4) by oxidative annealing, and then treats it in NaHB4 to achieve the evolution of its morphology and the construction of surface octahedral oxygen defects, and finally prepares double-shell Co3O4 nanospheres (DS-Co3O4-OVs) with octahedral oxygen vacancies and multi-level structures. In a suitable NaHB4 solution, irregular Co3O4 nanoparticles can evolve into a self-supporting two-dimensional nanosheet multi-level structure through Ost-Wald ripening reaction, and a large number of surface octahedral oxygen vacancies appear on the surface of each nanosheet, exposing more active sites and inhibiting the OER reaction, thereby achieving efficient electrocatalytic chlorine evolution.

[0005] In order to prepare a double-shell Co3O4 catalyst with octahedral oxygen vacancies on the surface with high electrocatalytic chlorine evolution selectivity, the present invention is based on Co-BTC precursor, and through oxidation annealing and defect engineering, double-shell Co3O4 nanospheres with octahedral oxygen vacancies and multi-level structure are constructed, achieving excellent catalytic performance, high stability, and high selectivity. The synthesis of the catalyst can be achieved through the following technical route: 1. A method for synthesizing a surface octahedral oxygen vacancy double-shell Co3O4 catalyst with high electrocatalytic chlorine evolution selectivity, comprising the following steps: ① Preparation of Co-BTC precursor: Cobalt nitrate hexahydrate, trimesic acid and an organic solvent are mixed and subjected to a solvothermal reaction to obtain a spherical precursor; the organic solvent comprises ethanol and ethylene glycol in a ratio of 1:0.5-5; the solvothermal reaction temperature is 130-160 °C and the solvothermal reaction time is 12-48 h; ② Preparation of DS-Co3O4 double-shell microspheres: The precursor obtained in step ① above is annealed and oxidized in air to obtain a Co3O4 material with a multi-level structure; the annealing temperature is 300~500 ℃, the annealing time is 1~3 h, and the annealing rate is 1~5℃ / min; ③ Preparation of DS-Co3O4-OVs double-shell microsphere structure containing surface octahedral oxygen vacancies: The DS-Co3O4 obtained in the above step ② is mixed with NaBH4 solution and immersed and stirred to obtain Co3O4 nanospheres with octahedral oxygen vacancies and a multi-level structure; the NaBH4 solution solvent is water, DS-Co3O4:NaBH4:water=1:5~10:1~10, and the stirring reaction time is 1~3h.

[0006] 2. The preparation method according to 1 is characterized in that: the Co-BTC obtained in step ① is a Co-metal organic framework material, which has a solid sphere with a smooth surface and a diameter of about 1~1.6 μm; the optimal ratio of Co(NO3)2·6H2O:H3BTC:ethanol:ethylene glycol is 3:1:0.5:1.

[0007] 3. The preparation method according to 1 is characterized in that: in the step ②, as the annealing rate decreases, the number of shell layers of DS-Co3O4 increases from one layer to two layers, wherein the optimal annealing temperature is 450°C and the annealing rate is 2°C / min; wrinkles appear on the surface of the DS-Co3O4 obtained after optimization, and the size is reduced compared to Co-BTC, with a diameter of about 0.7~1.1 μm, and a double shell structure appears inside.

[0008] 4. The preparation method according to 1 is characterized in that: the addition of NaBH4 in step ③ will immediately generate nanoparticles on the surface of DS-Co3O4, and as the reaction time increases, the nanoparticles rearrange to generate nanosheets with oxygen vacancies, and the size of the nanosheets gradually increases with time, about 100~500 nm; the reaction time has a significant effect on the number of oxygen vacancies on the surface of the microsphere structure and the morphology and phase of the product, and thus has a significant effect on the catalytic properties; the optimized optimal reaction time is 2 h, and the size of the nanosheets on the surface of DS-Co3O4-OVs is about 200 nm, which is a double-shell microsphere structure with octahedral oxygen vacancies.

[0009] 5. According to the preparation method described in 1, it is characterized in that: the DS-Co3O4-OVs prepared in step ③ has excellent chlorine evolution performance, and its chlorine selectivity is better than commercial ruthenium dioxide / iridium dioxide, and can be used as a high-performance non-precious metal-based electrocatalytic chlorine evolution catalyst.

[0010] As a further feature of the present invention, the optimized DS-Co3O4-OVs at 10 mA cm -2 Its CER overpotential is only 52 mV at a current density of 1.5 wt % and its chlorine evolution selectivity is as high as 98.9-99.9%, which is significantly better than commercial catalysts. After 60 hours of stability testing, its properties remain basically stable.

[0011] Due to the adoption of the above technical solution, the present invention has the following beneficial effects: In this experiment, the double-shell Co3O4 nanosphere morphology was formed by annealing Co-BTC, and then the irregular Co3O4 nanoparticles were directed to evolve into self-supporting two-dimensional nanosheets to construct hollow double-shell Co3O4 nanospheres (DS-Co3O4-OVs) under the action of sodium borohydride solution through aging reaction. A large number of surface octahedral oxygen vacancies appeared on the surface of each nanosheet. During the annealing process, due to the oxidative pyrolysis of organic ligands, a relatively stable Co3O4 shell was formed on the surface of Co-BTC microspheres. With further oxidation, the Co-BTC core gradually shrank. When the Co-BTC core was completely decomposed, a new Co3O4 shell would cover the surface of the Co-BTC core and further form a double Co3O4 shell structure. After being immersed in sodium borohydride solution, a large number of vertically grown nanosheets rich in octahedral oxygen vacancies were formed and covered on the surface of the microspheres through the maturation of Co3O4 nanoparticles, providing abundant accessible catalytic sites. The unique layered double-shell nanospheres and abundant surface octahedral oxygen vacancies can not only provide high surface area and fast mass transfer, but also the presence of oxygen defects can enhance the binding ability of the octahedral metal center to oxygen, inhibit the OER reaction, and improve the CER selectivity. -2 The best overpotential under the condition of 52 mV is achieved, and the selectivity for Cl2 is 98.9~99.9%, which is better than the existing RuO2 / IrO2. At the same time, after 65 hours of testing, the current is maintained at 95.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Scanning electron microscope image of Co-BTC obtained in Example 1; Figure 2 X-ray diffraction pattern of Co-BTC obtained in Example 1; Figure 3 Transmission electron microscopy image of Co-BTC obtained in Example 1; Figure 4 Scanning electron microscope image of DS-Co3O4 obtained in Example 1; Figure 5 Transmission electron microscopy image of DS-Co3O4 obtained in Example 1; Figure 6 X-ray diffraction pattern of DS-Co3O4 obtained in Example 1; Figure 7 Scanning electron microscope image of DS-Co3O4-OVs-1 obtained in Example 1; Figure 8 X-ray diffraction pattern of DS-Co3O4-OVs-1 obtained in Example 1; Fig. 9Electron paramagnetic resonance spectra of DS-Co3O4-OVs-1, DS-Co3O4-OVs-2, and DS-Co3O4-OVs-3 obtained in Examples 1, 2, and 3; Fig.10 CER curve of DS-Co3O4-OVs-1 obtained in Example 1; Fig.11 Scanning electron microscope image of DS-Co3O4-OVs-2 obtained in Example 2; Fig.12 Transmission electron microscopy image of DS-Co3O4-OVs-2 obtained in Example 2; Fig.13 X-ray diffraction pattern of DS-Co3O4-OVs-2 obtained in Example 2; Fig.14 CER curve of DS-Co3O4-OVs-2 obtained in Example 2; Fig.15 Chlorine selectivity curve of DS-Co3O4-OVs-2 obtained in Example 2; Fig.16 CER stability test curve of DS-Co3O4-OVs-2 obtained in Example 2; Fig.17 Scanning electron microscope image of DS-Co3O4-OVs-3 obtained in Example 3; Fig.18 Transmission electron microscopy image of DS-Co3O4-OVs-3 obtained in Example 3; Fig.19 X-ray diffraction pattern of DS-Co3O4-OVs-3 obtained in Example 3; Fig. 20 CER curve of DS-Co3O4-OVs-3 obtained in Example 3; Fig.21 Scanning electron microscope image of 1-DS-Co3O4-450 obtained in Example 4; Fig. 22 CER curve of 1-DS-Co3O4-450 obtained in Example 4; Fig.23 Scanning electron microscope image of 3-DS-Co3O4-450 obtained in Example 5; Fig.24 CER curve of 3-DS-Co3O4-450 obtained in Example 5. DETAILED DESCRIPTION

[0013] The technical features of the present invention are described below in conjunction with specific experimental schemes and drawings, but the present invention is not limited thereto. The experimental methods described in the following examples are conventional methods unless otherwise specified; the instruments and materials described are commercially available unless otherwise specified.

[0014] Example 1 A method for synthesizing a double-shell Co3O4 catalyst with octahedral oxygen vacancy on the surface and high selectivity for electrocatalytic chlorine evolution: ① Preparation of Co-BTC precursor: Mix cobalt nitrate hexahydrate, trimesic acid, and ethanol and ethylene glycol organic solvents in a volume ratio of 2:3. After the solution is evenly mixed, place it in a 150℃ environment for 24 hours for solvothermal reaction to obtain the target product Co-BTC. The morphology of Co-BTC is shown in its scanning electron microscope image ( Figure 1 ), the crystallinity of Co-BTC is shown in its powder X-ray diffraction pattern ( Figure 2 ), the internal morphology of Co-BTC is shown in its transmission electron microscope image ( Figure 3 ). The SEM and TEM of Co-BTC showed that the surface of the Co-BTC precursor was smooth and had a uniform solid nanosphere morphology with a diameter of about 1.6 μm; ② Preparation of DS-Co3O4 double-shell microspheres: The precursor obtained in step ① was heated to 450℃ in air at a rate of 2℃ / min for 2 h. After the reaction was completed, the temperature was naturally cooled to room temperature to obtain a double-shell hollow structure material DS-Co3O4. The morphology of DS-Co3O4 is shown in its scanning electron microscope image ( Figure 4 ), the internal morphology of DS-Co3O4 is shown in its transmission electron microscope image ( Figure 5 ) The crystallinity of DS-Co3O4 is shown in its powder X-ray diffraction pattern ( Figure 6 );

[0015] ③ Preparation of double-shell microsphere structure containing octahedral oxygen vacancies on the surface of DS-Co3O4-OVs: The DS-Co3O4 obtained in step ② above was immersed in NaBH4 solution and stirred for 1 h to obtain the final product, double-shell microsphere DS-Co3O4-OVs-1 containing octahedral oxygen vacancies on the surface. The morphology of DS-Co3O4-OVs-1 is shown in its scanning electron microscope image ( Figure 7 ), the crystallinity of DS-Co3O4-OVs-1 is shown in its powder X-ray diffraction pattern ( Figure 8 ), the oxygen vacancies of DS-Co3O4-OVs-1 are shown in the electron paramagnetic resonance spectrum ( Fig. 9 The CER properties were measured in a three-electrode system in sulfuric acid with a pH of 2 and containing 5 M sodium chloride as shown in the figure ( Fig.10), it can be calculated that (overpotential = actual test potential - 1.36 V, where 1.36 V is the standard electrode potential of CER), DS-Co3O4-OVs-1 has a high conductivity at a current density of 10 mA cm -2 When , the overpotential of CER is 68 mV.

[0016] Example 2 A method for synthesizing a double-shell Co3O4 catalyst with octahedral oxygen vacancy on the surface and high electrocatalytic chlorine evolution selectivity: ① The preparation of Co-BTC precursor is the same as in Example 1; ② The preparation of DS-Co3O4 is the same as in Example 1; ③ Preparation of double-shell microsphere structure containing octahedral oxygen vacancies on the surface of DS-Co3O4-OVs: immerse the DS-Co3O4 obtained in the above step ② in NaBH4 solution and stir for 2 h to obtain the final product, double-shell microsphere DS-Co3O4-OVs-2 containing octahedral oxygen vacancies on the surface. The morphology of DS-Co3O4-OVs-2 is shown in its scanning electron microscope image ( Fig.11 ), the internal morphology of DS-Co3O4-OVs-2 is shown in transmission electron microscopy ( Fig.12 ), the crystallinity of DS-Co3O4-OVs-2 is shown in its powder X-ray diffraction pattern ( Fig.13 ), the oxygen vacancies of DS-Co3O4-OVs-2 are shown in the electron paramagnetic resonance spectrum ( Fig. 9 The CER properties were measured in a three-electrode system in sulfuric acid with a pH of 2 and containing 5 M sodium chloride as the electrolyte, as shown in the figure ( Fig.14 ), it is calculated that DS-Co3O4-OVs-2 has a current density of 10 mA cm -2 When the overpotential of CER is 52 mV, the selectivity calculation properties are shown in the figure ( Fig.15 ), DS-Co3O4-OVs-2 has an excellent selectivity of 98.9~99.9% for Cl2, which is better than the existing RuO2 / IrO2. At the same time, the stability test curve is shown in the figure ( Fig.16 ), after 65 hours of testing, it still maintained 95.3% of the current.

[0017] Example 3 A method for synthesizing a double-shell Co3O4 catalyst with octahedral oxygen vacancy on the surface and high electrocatalytic chlorine evolution selectivity: ① The preparation of Co-BTC precursor is the same as in Example 1; ② The preparation of DS-Co3O4 is the same as in Example 1; ③ Preparation of double-shell microsphere structure containing octahedral oxygen vacancies on the surface of DS-Co3O4-OVs: immerse the DS-Co3O4 obtained in the above step ② in NaBH4 solution and stir for 3 h to obtain the final product, double-shell microsphere DS-Co3O4-OVs-3 containing octahedral oxygen vacancies on the surface. The morphology of DS-Co3O4-OVs-3 is shown in its scanning electron microscope image ( Fig.17 ), the internal morphology of DS-Co3O4-OVs-3 is shown in transmission electron microscopy ( Fig.18 ), the crystallinity of DS-Co3O4-OVs-3 is shown in its powder X-ray diffraction pattern ( Fig.19 ), the oxygen vacancies of DS-Co3O4-OVs-3 are shown in the electron paramagnetic resonance spectrum ( Fig. 9 The CER properties were measured in a three-electrode system in sulfuric acid with a pH of 2 and containing 5 M sodium chloride as the electrolyte, as shown in the figure ( Fig. 20 ), it is calculated that DS-Co3O4-OVs-3 has a current density of 10 mA cm -2 When , the overpotential of CER is 84 mV.

[0018] Example 4 A method for synthesizing a double-shell Co3O4 catalyst with octahedral oxygen vacancy on the surface and high electrocatalytic chlorine evolution selectivity: ① The preparation of Co-BTC precursor is the same as in Example 1; ② Preparation of DS-Co3O4 double-shell microspheres: The precursor obtained in step ① was heated to 450°C in air at a rate of 1°C / min for 2 h. After the reaction was completed, the temperature was naturally cooled to room temperature to obtain a double-shell hollow structure material 1-DS-Co3O4-450. The morphology of 1-DS-Co3O4-450 is shown in its scanning electron microscope image ( Fig.21 ), the CER properties were measured in a three-electrode system in sulfuric acid with a pH of 2 and containing 5 M sodium chloride as shown in the figure ( Fig. 22 ), it is calculated that 1-DS-Co3O4-450 has a current density of 10 mA cm -2 When , the overpotential of CER is 157 mV.

[0019] Example 5 A method for synthesizing a double-shell Co3O4 catalyst with octahedral oxygen vacancy on the surface and high electrocatalytic chlorine evolution selectivity: ① The preparation of Co-BTC precursor is the same as in Example 1; ② Preparation of DS-Co3O4 double-shell microspheres: The precursor obtained in step ① was heated to 450°C in air at a rate of 3°C / min for 2 h. After the reaction was completed, the temperature was naturally cooled to room temperature to obtain a double-shell hollow structure material 3-DS-Co3O4-450. The morphology of 3-DS-Co3O4-450 is shown in its scanning electron microscope image ( Fig.23 ), the CER properties were measured in a three-electrode system in sulfuric acid with a pH of 2 and containing 5 M sodium chloride as the electrolyte, as shown in the figure ( Fig.24 ), it is calculated that 3-DS-Co3O4-450 has a current density of 10 mA cm -2 When , the overpotential of CER is 186 mV.

[0020] The description of the embodiments disclosed in the present invention is not intended to limit the scope of the present invention, but is used to describe the present invention. Accordingly, the scope of the present invention is not limited by the above embodiments, but is defined by the claims or their equivalents.

Claims

1. A method for synthesizing a surface octahedral oxygen vacancy double-shell Co3O4 catalyst with high electrocatalytic chlorine evolution selectivity, comprising the following steps: ① Preparation of Co-BTC precursor: Cobalt nitrate hexahydrate, trimesic acid and an organic solvent are mixed and subjected to a solvothermal reaction to obtain a spherical precursor; the organic solvent comprises ethanol and ethylene glycol in a ratio of 1:0.5-5; the solvothermal reaction temperature is 130-160 °C and the solvothermal reaction time is 12-48 h; ② Preparation of DS-Co3O4 double-shell microspheres: The precursor obtained in the above step ① is annealed and oxidized in air to obtain a Co3O4 material with a multi-level structure; the annealing temperature is 300~500 ℃, the annealing time is 1~3 h, and the annealing rate is 1~5 ℃ / min; ③ Preparation of DS-Co3O4-OVs double-shell microsphere structure containing surface octahedral oxygen vacancies: The DS-Co3O4 obtained in the above step ② is mixed with NaBH4 solution and immersed and stirred to obtain Co3O4 nanospheres with octahedral oxygen vacancies and a multi-level structure; the NaBH4 solution solvent is water, and the stirring reaction time is 1~3 h.

2. The synthesis method according to claim 1, characterized in that: The Co-BTC obtained in step ① is a Co-metal organic framework material, which has a solid sphere with a smooth surface and a diameter of about 1-1.6 μm.

3. The synthesis method according to claim 1, characterized in that: The surface of the DS-Co3O4 obtained after optimization in step ② is wrinkled, and its size is smaller than that of Co-BTC, with a diameter of about 0.7~1.1 μm, and a double shell structure appears inside.

4. The synthesis method according to claim 1, characterized in that: In the step ③, the size of the DS-Co3O4-OVs surface nanosheets is about 200 nm, and they are double-shell microsphere structures with octahedral oxygen vacancies.

5. The use of the catalyst synthesized by the synthesis method according to claim 1, characterized in that: The catalyst DS-Co3O4-OVs can be applied to the field of electrocatalytic chlorine evolution.

Citation Information

Cited By

  • Preparation method of Co-based oxide nanosheet based on oxygen vacancy regulation and control reaction mechanism and acidic oxygen evolution application of Co-based oxide nanosheet

    CN120683551A